2015
DOI: 10.1177/0194599814564536
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Temporal Bone Osteoradionecrosis

Abstract: Ramsden's classification system is clinically relevant in predicting conservative treatment outcomes. Mastoid air cell destruction on computed tomography differentiates between the localized and diffuse forms of ORN. Given our results and experience with treating temporal bone ORN, we propose a treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 7 publications
2
25
0
1
Order By: Relevance
“…Anatomical features are suggested to facilitate necrosis of this region, such as the superficial nature of the temporal bone, thin overlying skin and weak blood supply. Furthermore, it has been proposed that continuity with the upper respiratory tract by means of the Eustachian tube allows access of pathogens to this region. Interestingly, all these factors are principally those proposed for the cause of ORN of the jaws such as thin oral mucosa, poor mandibular blood supply and oral microflora.…”
Section: Temporal Bone Ornmentioning
confidence: 99%
“…Anatomical features are suggested to facilitate necrosis of this region, such as the superficial nature of the temporal bone, thin overlying skin and weak blood supply. Furthermore, it has been proposed that continuity with the upper respiratory tract by means of the Eustachian tube allows access of pathogens to this region. Interestingly, all these factors are principally those proposed for the cause of ORN of the jaws such as thin oral mucosa, poor mandibular blood supply and oral microflora.…”
Section: Temporal Bone Ornmentioning
confidence: 99%
“…11,25 The latency period between radiation exposure and the development of ORN-related symptoms averages approximately 8 years, but the range varies widely from 6 months to 48 years. 1,4,10,11,[16][17][18][19] In their series of 33 patients, Sharon et al found no correlation between radiation dose to the primary site and the time to development of ORN. 17 Ramsden et al suggested that patients younger than 40 years at the time of radiation exposure seemed to present after longer latency periods than patients older than 40 years (8 vs. 6 years).…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that the two previous schemes demonstrate significant overlap with Ramsden's localized form translating to Morrissey grade I/II and diffuse disease with grade III/IV. 16 They also suggested that the severity of symptoms in patients with diffuse ORN may be a relevant parameter for distinguishing between appropriate treatment modalities, noting that a subgroup of patients with diffuse disease but fewer symptomatic complaints were treated with conservative measures and that nearly half achieved therapeutic goals (►Table 1). 16…”
Section: Diagnosis and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ha ugyanazon intézet több közleményt is közzétett, akkor mindig a frissebb, vagy a nagyobb beteganyagot bemutató közleményt vettük alapul. A 10 legnagyobb beteganyagot feltüntető közleményt alapul véve, utalni kívántunk a patológia, a komplikációk, valamint a sebészi technika nevezéktanának változatosságára [16][17][18][19][20][21][22][23][24][25].…”
Section: Az Irodalom áTtekintéseunclassified